Hadith Istinbath Methodology: A Comparative Review between Salafiyah Scholars and Persatuan Islam (PERSIS) - Permana, Robi; Muslimin, JM (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2024)
This study explores the comparative methodologies of legal deductions (istinbath) between Salafi scholars and Persatuan Islam (PERSIS) in applying hadith as a source of Islamic law. Salafi scholars adopt a textual approach to interpreting hadith, whereas PERSIS prefers a contextual approach that considers social conditions and the clear meaning of the hadith. The Salafi approach tends to yield stricter and less flexible legal conclusions, whereas PERSIS is more open to changes and relevance in modern times. This article highlights how these methodological differences significantly impact legal rulings on issues such as the isbal, beard maintenance, and wearing of the niqab. The research employs a descriptive qualitative approach, analysing various primary and secondary sources related to hadith-based legal methodology.